THE DISSOLUTION KINETICS OF QUARTZ IN AQUEOUS MIXED CATION SOLUTIONS - OH- CATALYSIS - Dove P.M. (My University, 1999)
The dissolution kinetics of quartz is quantified in dilute mixtures of magnesium, calcium, barium, and sodium chloride salts in near-neutral pH solutions over the temperature range of 175 to 295°C. Measurements using single-salt solutions show that the rate-enhancing effects increase in the order: Mg2+ < Ca2+ ~ Na+ < Ba2+. Barium ion increases dissolution rates by 114x compared to new, slower rates found for deionized water (10-8.41) at 200°C. Experimental activation energies, Exp, measured for each salt solution are similar within experimental errors. In solution mixtures of two salts, dissolution rates are a nonlinear combination of the bulk concentrations of cations in solution such that rates are limited by the cation with the smallest rate-enhancing effect. That is, a small fraction of magnesium ion in the mixture limits the net dissolution rate to an extent disproportionate to its bulk concentration. This behavior is more pronounced for salt mixtures of 2+ : 1+ cations (i.e. Mg2+ and Na+) than 2+ : 2+ cations (i.e. Mg2+ and Ba2+ or Ca2+).The behavior observed in salt mixtures is quantified by an empirical expression based on a competitive cation-surface interaction model. The kinetic model assumes that salt-enhanced dissolution rates are determined by the intrinsic ability of each type of cation, i, to enhance rates (kmx,i) and their concentration(s) at the surface (Kad,i). Estimates of these parameters are obtained by fitting the model to data from the rate versus concentration experiments conducted in single-salt solutions. The resulting kinetic expression gives good predictions of rates measured in salt mixtures and is consistent with previous models of cation-enhanced dissolution kinetics of quartz. The model predicts that magnesium and calcium have greater roles in regulating quartz dissolution rates despite lower concentrations in natural waters than sodium and potassium because of their larger surface interaction strengths.